Dynamics of change and effectiveness of development banks : a view from the DFL - Pemberton, Gerard ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Provides a perspective on change and effectiveness in development banking based on the experience of Development Finance Limited (DFL) from 1991. Suggests the reason why this type of institution should be considered a necessary part of the region's financial structure. Outlines briefly, some of the factors which will affect development banks in the region over the next five years.